Fruit and Vegetable Shopping Behavior and Intake among Low-Income Minority Households with Elementary-Aged Children - Brittni N. Metoyer; Ru-Jye Chuang; MinJae Lee; Christine Markham; Eric Brown; Maha Almohamad; Jayna M. Dave; Shreela V. Sharma (MDPI AG, 2022)
Low-income children and families do not meet the recommendations for fruit and vegetable (FV) intake. This study aimed to assess the association between FV shopping behavior and child FV intake through a cross-sectional study design analyzing self-reported surveys (n = 6074) from adult-child dyads of Hispanic/Latino and African American participants enrolled in the Brighter Bites co-op program. Through quantitative mixed effects linear regression models, accounting for school-level clustering and adjusting for covariates, child FV intake was positively associated with shopping for FV at large chain grocery stores (p < 0.001), natural/organic supermarkets (p < 0.001), warehouse club stores (p = 0.002), discount superstores (p < 0.001), small local stores/corner stores (p = 0.038), convenience stores (p = 0.022), ethnic markets (p = 0.002), farmers' markets/co-op/school farm stands (p < 0.001), and gardens (p = 0.009) among Hispanic/Latinos participants. Among African American participants, there was significant positive association between child FV intake and shopping for FV at natural/organic supermarkets (p < 0.001), discount superstores (p = 0.005), and convenience stores (p = 0.031). The relationship between location and frequency of shopping for FV and child FV intake varied between races. Further research is needed to better understand the influence of cultural and physical environmental factors. Nutrition education programs are vital to encouraging families to make healthier food choices and purchases to improve child FV consumption.